Population Projection And Water Demand Forecasting In Nong District, Savannakhet Province, Lao PDR - Phoummixay Siharath; Keoduangchai Keokhamphui; Ketkeo Kounvong; Somchay Vilaychaleun; Soulyphan Kannitha; Chankhachone Sonemanivong; Khampasith Thammathevo; Phaiphana Siharath (Sean Institute, 2025)
Water is an essential factor and pay a vital important role for the livelihood of the human, since, increasing of the people, it causes on high water demand either urban or sub-urban city, the objective of the study is to project the population and also forecast the water demand within Nong district, by employing the statical analysis and technical method to predict the water demand, therefore, the research found that with the 1.7% of population growth rate, in 2019, 2024, 2029, 2034 and 2039, average water demand is 279 m3/d, 324 m3/d, 360 m3/d, 399m3/d and 434m3/d and maximum water demand is 388 m3/d, 433 m3/d, 479 m3/d and 521m3/d, respectively.